Rooted on the Coast: Ecofeminism and Ecological Resilience in the Mangrove Forests of Tanjung Siambang, Kepulauan Riau Province, Indonesia - Damai Vistiani Gulo; Siti Arieta; Nikodemus Niko (Jurnal Sosiologi Nusantara, 2025)
This study explores ecofeminism in the sustainable management of mangrove forests in Tanjung Siambang. Employing a qualitative method with a descriptive approach, data were collected through observation, in-depth interviews, and documentation. The research focused on women who are actively involved in mangrove conservation, environmental activists, and community members with local ecological knowledge and skills. The findings reveal a significant connection between women and nature, where women play a central role in mangrove management based on traditional ecological knowledge. Their practices emphasize conservation without causing environmental harm and are rooted in a deep understanding of the local ecosystem. Furthermore, women are not only preserving mangrove forests but also transforming them into sources of sustainable livelihoods. Despite facing structural barriers such as patriarchal cultural norms, these challenges have not deterred their efforts. Instead, they serve as motivation for women to assert their agency in ecological governance. This research highlights how women in Tanjung Siambang integrate ecological responsibility with economic empowerment, demonstrating that ecofeminism is not only a critique of environmental degradation and gender inequality but also a practical framework for sustainable community-based environmental management.